1998
DOI: 10.1037/h0087845
|View full text |Cite
|
Sign up to set email alerts
|

The effects of DSM-IV cluster B personality disorder symptoms on the termination and continuation of psychotherapy.

Abstract: This study investigates the relationship between therapy attendance with DSM-IV criteria for the cluster B personality disorders (antisocial [ANPD]; borderline [BPD]; histrionic [HPD]; and narcissistic [NPD]). Ninety patients who were found to meet DSM-IV criteria for an Axis II disorder (clusterA personality disorders = 10; ANPD = 20, BPD = 25, HPD = 5, NPD = 14; cluster C personality disorders = 16).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 90 publications
4
38
0
1
Order By: Relevance
“…These studies highlight the importance of a careful understanding of the interpersonal aspects of BP. Of additional importance is past research that has reported the importance of the therapeutic relationship with this specific clinical population (Cohen & Sherwood, 1989;Gunderson et al, 1989;Hilsenroth, Holdwick, Castlebury, & Blais, 1998 Koenigsberg, Carr, & Appelbaum, 1989;Sandell et al, 1993;Steiger & Stotland, 1996;Summers, 1999;Yeomans, Selzer, & Clarkin, 1993;Yeomans et al, 1994). As such, improved understanding of the interpersonal characteristics of BPD may help clinicians more effectively navigate the relational intricacies inherent to the development of an effective working alliance (see e.g., Gurtman, 1996).…”
Section: Implications For Treatmentmentioning
confidence: 94%
“…These studies highlight the importance of a careful understanding of the interpersonal aspects of BP. Of additional importance is past research that has reported the importance of the therapeutic relationship with this specific clinical population (Cohen & Sherwood, 1989;Gunderson et al, 1989;Hilsenroth, Holdwick, Castlebury, & Blais, 1998 Koenigsberg, Carr, & Appelbaum, 1989;Sandell et al, 1993;Steiger & Stotland, 1996;Summers, 1999;Yeomans, Selzer, & Clarkin, 1993;Yeomans et al, 1994). As such, improved understanding of the interpersonal characteristics of BPD may help clinicians more effectively navigate the relational intricacies inherent to the development of an effective working alliance (see e.g., Gurtman, 1996).…”
Section: Implications For Treatmentmentioning
confidence: 94%
“…Two studies have examined the impact of narcissistic traits on early dropout from therapy. Using a retrospective record-review method to diagnose personality disorder symptoms, Hilsenroth, Holdwick, Castlebury, and Blais (1998) found that if outpatients met the "requires excessive admiration" criterion for NPD, they were more likely to drop out prematurely from long-term psychodynamic psychotherapy. Although the reliability of these retrospective ratings was adequate, it is unclear whether the information contained in patient records and the coding procedures used resulted in a valid assessment of narcissistic pathology.…”
Section: Pathological Narcissism and Psychotherapymentioning
confidence: 99%
“…Zu− dem ist zusätzlich mit einer sehr hohen Abbruchswahrschein− lichkeit seitens des Patienten zu rechnen. Hilsenroth et al [74] berichten eine Abbruchrate von 64 %, wobei sich das vierte diag− nostische Kriterium nach DSM−IV (¹verlangt nach übermäßiger Bewunderung") als signifikantester Prädiktor für den Abbruch erwies. Bisher gibt es nur sehr wenige Untersuchungen, die prognosti− sche Aussagen zulassen.…”
Section: Prognoseunclassified